Electrocardiogram in patients with acute inferior myocardial infarction due to occlusion of circumflex artery. Issue 42 (October 2017) - Li, Qun; Wang, De-Zhao; Chen, Bu-Xing
Abstract : Abstract: To investigate the diagnostic value of electrocardiographic (ECG) ST-segment in acute inferior myocardial infarction (AIMI) caused by the left circumflex branch (LCX). A total of 240 clinical cases with AIMI in our hospital were retrospectively analyzed. All of them had received percutaneous coronary intervention (PCI) within 12 hours after symptom onset. The clinical features, ECG manifestations, and coronary artery lesion characteristics of the patients were collected. The right coronary artery (RCA) was shown to be the infarct-related artery (IRA) in 177 patients, while LCX was responsible for AIMI in 63 cases. There was no significant difference in the risk factors of coronary heart disease (CHD) ( P > .05 for all) between the 2 groups. ST-segment elevation in lead II, III, and AVF could be found in all patients. Moreover, ST-segment depression in lead I (STD I), ST-segment elevation in lead III (STE III), STE III-STE II, STE AVF, STD AVL, STD AVL-STD I and STE v6 lead ST-segment deviation exhibited significant difference in 2 groups ( P < .05 for all). The changes of STD I, STE III < STEII, STD AVL < STD I could discriminate between LCX and RCA in AIMI patients with high sensitivity and specificity. ECG may be an effective tool to predict the IRA in patient with AIMI.